The Benefits and Obstacles to Perspective Getting - Damen, Debby; Pollmann, Monique M. H.; Grassow, Teri-Louise (Frontiers in Communication, 2021)
In general, people tend to rely on egocentric projection when predicting others’ emotions, attitudes, and preferences. However, this strategy is less effective than the more obvious strategy of directly asking others what they feel, think, or desire (‘perspective getting’). In three experimental studies, we investigated how likely people are to ask for others’ perspectives, whether it leads to better predictions, and what factors impede perspective getting. In the first study, we let participants predict how happy another person would be with different money distributions. Only 26% of all people engaged in perspective getting, and it did not lead to better predictions. In the second study, we let people predict how expensive another person would think certain products are. The majority of people engaged in some form of perspective getting, but only 23% of all people did this thoroughly. Perspective getting did lead to better predictions. In the final study, we let people predict another person’s attitudes about a wide range of topics. Here, 70% of the people engaged in perspective getting and 12.5% did so thoroughly. Again, perspective getting led to better predictions. We found that confidence acted as a barrier for perspective getting. We also tested whether pointing out that perspective getting is the best strategy would increase perspective getting. We do not find a positive effect of this intervention. We discuss possible other interventions to increase people’s tendency to get rather than take perspective.